Plagiarisme pada Karya Ilmiah Mahasiswa Semester Akhir UIN Mataram Tahun 2020-2021 - Asnawati Asnawati (UPT Perpustakaan UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
Plagiarism is a very serious behavior that occurs in the world of education until now. This needs to be taken seriously because it has an unhealthy impact on the world of education. In minimizing the number of fraudulent scientific writing for UIN Mataram students. This study aims to provide an overview of the extent to which students' abilities in making scientific works without plagiarism are beyond the specified threshold. With the help of IT, it is hoped that the students' ability to produce original works is more honed and more competitive. This research uses descriptive qualitative method by using informants. The informants in this study were students and librarians and were selected using a purposive sampling technique. This data was obtained through the process of documents stored through the data base of the Mataram UIN Library with the turnitin application, thus providing more accurate information. With the help of the turnitin application, this research makes a real contribution in determining the policies taken by the UPT Library of UIN Mataram to all policy makers in the relevant institutions